Adsorption and desorption of hydroxychloroquine onto sulphur doped graphene powders as a potential drug for COVID-19: physicochemical investigation, surface chemistry and in vitro cytotoxicity evaluation - Acar, Tayfun; Arvas, Melih Besir; Arvas, Busra; Ucar, Burcu; Sahin, Yucel (SPRINGER, 2024)
Hydroxychloroquine (HCQ) is a very substantial drug active substance that was approved for emergency use by the FDA during the peak of the COVID-19 pandemic due to its potent antiviral properties. In this study, adsorption and desorption of hydroxychloroquine on sulfur (S)-doped graphene powders were investigated. While the adsorption experiments were carried out in the environment of distilled water (pH 5.0-6.0), HEPES buffer (pH 7.6), and Tris.HCl buffer (pH 8.0) the desorption studies were performed in distilled water. The HCQ adsorbed S-doped graphene powders were characterized by UV-Vis, FT-IR, XRD, BET and TEM techniques. According to UV-Vis measurements, the adsorption efficiency in the HEPES buffer medium at pH 7.6 was the highest (68.72% for H3 (HCQ adsorption with SGr3 graphene in HEPES medium)). FT-IR and XRD analyses confirmed the presence of HCQ on the graphene powders' surface. While morphological changes on the surfaces of graphene powders were imaged by TEM, BET surface area changes proved the HCQ adsorption. The in vitro toxicity of the developed H3 was found to be lower than that of HCQ alone on the L929 cell line. These fundamental findings of the surface interaction between HCQ and graphene are precious for the design and optimization of a targeted drug based on this molecule and material. The adsorption/desorption features of HCQ onto graphene-based carrier systems which in particular doped with sulfur from functional metals have been investigated for the first time.
Keywords: Adsorption; Desorption; Sulfur doped graphene; Hydroxychloroquine; COVID-19; CHLOROQUINE; NITROGEN; Chemistry; Engineering